Implementation of Government Accounting Standards Statement (PSAP) Number 05 Concerning Inventory Accounting at the Minanga Community Health Center, Manado City - Manarisip, Villy Putry Marjelitha; Morasa, Jenny; Walandouw, Stanley Kho (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research evaluates the application of Government Accounting Standards Statement (PSAP) Number 05 concerning inventory accounting at the Minanga Community Health Center, Manado City. PSAP Number 05 regulates the recognition, measurement and disclosure of inventories in government financial reports. The methods used include observation, interviews and document analysis. The research results show that inventory recognition and measurement are in accordance with standards, such as the application of the FIFO method and acquisition costs. However, inventory disclosure in the Notes to Financial Reports (CALK) is less detailed. This research recommends improvements in disclosure to increase transparency and compliance with PSAP 05, as well as providing a reference for improving accounting practices in government health institutions.